2002
DOI: 10.1007/s00247-001-0569-3
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal compartment syndrome in children: CT findings

Abstract: Abdominal compartment syndrome (ACS) is caused by pathological elevation of intra-abdominal pressure (IAP) leading to multiple organ dysfunction syndrome. Since the condition is highly lethal, early diagnosis is imperative. We evaluated the pre-operative abdominal CT scans of three children with proven ACS to identify signs of elevated IAP. Findings common to these patients included narrowing of the inferior vena cava (IVC), direct renal compression or displacement, bowel wall thickening with enhancement and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…Peak airway pressure and 24-h fluid balance are two independent variables that can be used to predict the development of ACS in non-trauma surgical patients 51 . Computed tomographic changes have also been reported, such as narrowing of the IVC, direct renal compression and bowel wall thickening with a rounded abdomen 55 . Methods for diagnosing ACS at an earlier stage are being developed; these are based on early evidence of splanchnic hypoperfusion and acidosis.…”
Section: Early Detection Of Abdominal Compartment Syndromementioning
confidence: 96%
“…Peak airway pressure and 24-h fluid balance are two independent variables that can be used to predict the development of ACS in non-trauma surgical patients 51 . Computed tomographic changes have also been reported, such as narrowing of the IVC, direct renal compression and bowel wall thickening with a rounded abdomen 55 . Methods for diagnosing ACS at an earlier stage are being developed; these are based on early evidence of splanchnic hypoperfusion and acidosis.…”
Section: Early Detection Of Abdominal Compartment Syndromementioning
confidence: 96%
“…Only a few small studies have identified characteristic CT imaging features of IAH and ACS [4][5][6][7][8]. Key to ACS management is acknowledging that IAH is secondary to underlying pathology, frequently systemic inflammatory response syndrome (SIRS), bleeding, or fluid extravasation [9].…”
Section: Computed Tomographymentioning
confidence: 99%
“…Although ACS is typically identified clinically (14), intravesicular pressure monitoring (15) and CT abdominal imaging (8 -11) aid in ACS diagnosis. CT analyses of ACS in adult (8) and pediatric (10,11) patients show free peritoneal fluid, inferior vena cava compression, and bowel wall thickening and enhancement. The "round belly sign" on CT is diagnostic of ACS in adult patients (100% sensitivity, 94% specificity) as an anteroposterior-to-transverse abdominal ratio Ͼ0.80, measured at the level of the left renal vein (8).…”
Section: Discussionmentioning
confidence: 97%